The Role of Hope and Emotional Maturity Which Influence Forgiveness in College Students Who Have Experienced Breakup - Nina, Qurrota Ayu; Mujidin, Mujidin (Jurnal Sains Psikologi, 2023)
This study aims to examine the effect of emotional maturity empirically and hope on forgiveness in college students who have experienced a breakup. The research method used is the quantitative method with a cross-sectional study design. This study’s population was college students who had experienced a breakup in the last five years using a purposive random sampling technique. The measuring instruments in this study used the hope scale, emotional maturity scale, and forgiveness scale. The data analysis used to test the hypothesis is multiple linear regression analysis. Based on the results of multiple regression analysis for the major hypothesis, the F value of hope and emotional maturity on forgiveness is 60.167 with a significance level (p) of 0.000 (p less than 0.01). This means there is a significant influence between hope and emotional maturity on forgiveness. The effective contribution separately on the hope variable on forgiveness is 8 percent, and the contribution of emotional maturity to forgiveness is 35 percent. The total effective contribution is 43 percent, with the remaining 47 percent effective contribution to forgiveness influenced by other variables not discussed in this study. This research is expected to contribute to the scientific field of psychology, especially positive psychology. In addition, it is also expected to be a reference for further research and practically to find out the role of hope and emotional maturity that affects forgiveness in college students.